Impact of share pledging by controlling shareholders on firm value in the context of China’s tightened regulatory reforms - Su, Zili; Alexiou, Constantinos (Wiley, 2022)
This study investigates the effect of the 2018 regulatory reforms of share pledging by a controlling shareholder on firm value in China. Using a dataset spanning the period 2015 to 2020, we provide robust results suggesting that tighter regulations effectively reduce firms' crash risk, relax financial constraints, reduce bankruptcy risk, and mitigate the controlling shareholder expropriation of minority shareholders' wealth via tunnelling. Additionally, controlling shareholders, by investing more pledged funds in the listed firm after reforms, foster capital investment and R&D expenditure, which benefit firm growth and competitiveness and ultimately increase firm long-term value.
Keywords: Share Pledging; Regulatory Reforms; Firm Value; R&D